Factors associated with bereaved family surrogates' satisfaction with end-of-life care in intensive care units. (August 2022) - Chiang, Ming Chu; Huang, Chung-Chi; Hu, Tsung-Hui; Chou, Wen-Chi; Chuang, Li-Pang; Tang, Siew Tzuh
Abstract: Objectives: Family satisfaction with end-of-life care in the intensive care unit constitutes an important outcome for evaluating end-of-life care quality. Research on this topic focuses on linking end-of-life care processes to family-surrogate satisfaction with the patient's end-of-life care but has seldom examined patient- and family-surrogate-based factors. We aimed to comprehensively and simultaneously examine factors facilitating or deterring family satisfaction with end-of-life care in the intensive care unit from patient- and family-surrogate perspectives. Methods: For this secondary-analysis study, 278 Taiwanese family surrogates were surveyed one-month post-patient death using the Family Satisfaction in the Intensive Care Unit questionnaire (FS-ICU), which measures care and decision-making. Associations between family satisfaction with end-of-life care and patient and family characteristics, patient disease severity, and length of intensive care stay were examined by multivariate, multilevel linear regression models. Results: Female family surrogates were more satisfied with patients' end-of-life care than male family surrogates when patients had a higher APACHE II but a lower SOFA score. Adult-child surrogates had lower FS-ICU Care scores than other family surrogates. Higher satisfaction with ICU decision-making was associated with patients' higher APACHE II but lower SOFA scores, longer stay and family socio-demographics, including being unmarried, educational attainment above junior high school and reported financial sufficiency to make ends meet. Conclusion: Patient disease severity and family-surrogate characteristics are significantly associated with surrogates' satisfaction with patients' end-of-life care in the intensive care unit. Specific interventions should be tailored to the needs of high-risk family surrogates to increase their satisfaction with this care.